2018
DOI: 10.1371/journal.pgen.1007802
|View full text |Cite
|
Sign up to set email alerts
|

A natural antisense lncRNA controls breast cancer progression by promoting tumor suppressor gene mRNA stability

Abstract: The human genome encodes thousands of long noncoding RNA (lncRNA) genes; the function of majority of them is poorly understood. Aberrant expression of a significant number of lncRNAs is observed in various diseases, including cancer. To gain insights into the role of lncRNAs in breast cancer progression, we performed genome-wide transcriptome analyses in an isogenic, triple negative breast cancer (TNBC/basal-like) progression cell lines using a 3D cell culture model. We identified significantly altered express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
93
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(98 citation statements)
references
References 78 publications
3
93
2
Order By: Relevance
“…Functionally, dysregulation of lncRNAs is closely associated with aberrant biological behaviors of human cancers [28]. It is noteworthy some lncRNAs oriented in antisense direction with respect to a protein coding loci in the opposite strand usually act as regulators in many pathological processes [29]. Previous studies have shown that the natural antisense transcripts play critical roles in various physiological and pathological processes through regulating gene promoter activation and transcription [30][31][32].…”
Section: Discussionmentioning
confidence: 99%
“…Functionally, dysregulation of lncRNAs is closely associated with aberrant biological behaviors of human cancers [28]. It is noteworthy some lncRNAs oriented in antisense direction with respect to a protein coding loci in the opposite strand usually act as regulators in many pathological processes [29]. Previous studies have shown that the natural antisense transcripts play critical roles in various physiological and pathological processes through regulating gene promoter activation and transcription [30][31][32].…”
Section: Discussionmentioning
confidence: 99%
“…SHAP value in gene expression showed that RBM20 gene expression contributed more in luminal B subtype than other subtypes (Figure 5D). The finding is accordant with the public results which proves that RBM20 gene expression is correlated with PDCD4-AS1/PDCD4, a tumor suppressor in TNBC cell lines 29 and a subset of TNBC potentially benefit therapy targeting luminal subtype’s typical pathways 30 . In other examples, the SHAP value of TFAP2B shows it is an important gene feature in breast cancer (Figure 5D).…”
Section: Resultssupporting
confidence: 79%
“…For instance, Sun and colleagues reported that lncRNA HOXA11‐AS promoted gastric cancer tumorigenesis through functioning as scaffold of chromatin modification factors LSD1, PRC2, and DNMT1 . In addition, lncRNA PDCD4‐AS1 contributes to breast cancer progression by stabilizing PDCD4 mRNA through forming RNA duplex and controlling PDCD4 mRNA’s interaction with RNA decay promoting factor HuR . Moreover, LINC01234 promotes the malignancy of gastric cancer via acting as a competing endogenous RNA for miR‐204‐5p to regulate CBFB expression …”
Section: Introductionmentioning
confidence: 99%